Organizational and behavioral determinants of health information system performance in Iraq - M, Thaer E; Alrubaey, Mazin Gh (AL-Kindy College Medical Journal, 2015)
Background: Health information systems in most countries are inadequate in providing the needed management support and the current health information systems are therefore widely seen as management obstacles rather than as tools,Objectives: the current study is an attempt to assess the behavioral and organizational determinants of health information system performance in Iraq.Methods: A cross-sectional study was conducted by interviewed a total of 189 respondents selected from six Iraqi governorates. The Organizational and Behavioral Assessment Tool was used to measure the behavioral and organizational determinants of health information system performance, it is one of the PRISM package tools that are used to assess the health information system performance.Results: The overall mean confidence for Health information system tasks was 69.41%, while for tasks competence, it was 37.1% and that of motivation level was 43.4%. The totalscore of promoting a culture of information was 63.96% with department provide reward for a good work revealed a total percent of 56.83%.Conclusion: It can be concluded that overall mean confidence for Health information system tasks is generally high compared to a low competency level for Health information system tasks, with a negative motivation feeling among respondents.Keywords: Health information system, organizational and behavioral determinant, OBAT tool, culture of information.